Breastfeeding practices, consumption of ultra-processed foods in complementary feeding and associated factors in premature children - Parreiras, Emanuelle Emília Ferreira; Lima, Luciana Moreira; Pereira, Ronaldo Cascelli Schelb Scalla; Serafim, Tatiane Cristina; Figueiredo, Luiz Felipe Gonçalves de; Moreira, Daniela Rezende; Rodrigues, Simone Cunha Magalhães; Freitas, Brunnella Alcantara Chagas de (Ciência e Natura, 2022)
Breastfeeding and a suitable eating plan in the first years of life are crucial for the development of premature children. Early exposure to ultra-processed foods (UPF) can lead to an increased risk of chronic diseases. To analyze premature infants for breastfeeding practices, intake of ultra-processed foods, their health risks and other associated factors. Data on diet and sociodemographic variables were investigated using questionnaires. We used anthropometric assessment according to WHO growth curves and laboratory tests to analyze the lipid profile. From the whole sample, 51% never received exclusive breastfeeding, or received it for less than a single month; 29% received between four and six months; in 84% another food was introduced before six months. After the stratification of consumption between “none/one type” and “more than one type” of UPF, the variables “child's age” and “family history of overweight/obesity” were positively associated. After bivariate and multivariate analyzes, a greater diversity of UPF intake was associated with family income <2 minimum wages and employed mothers. Premature infants are at risk of early weaning and use of AUP before even six months of corrected age.